The impact of putting a surgical drain in total knee arthroplasty on the postoperative hemoglobin level - AlShaqsi, Ziyad; Alhabsi, Khalil; AlLawati, Ali Abdullah Mohammed (International Journal of Research in Orthopaedics, 2025)
Background: The use of suction drains following total knee arthroplasty (TKA) remains controversial, with conflicting evidence regarding their impact on postoperative blood loss and hemoglobin levels.1 To evaluate the impact of closed negative suction drainage on postoperative hemoglobin levels following primary unilateral total knee arthroplasty. Methods: A retrospective cohort study was conducted involving 102 patients who underwent primary unilateral TKA. Patients were divided into two equal groups: 51 with closed suction drainage and 51 without drainage. Hemoglobin levels were measured preoperatively and 24 hours postoperatively. Statistical analysis was performed using SPSS with appropriate tests for continuous and categorical variables. Results: No significant difference was observed in the hemoglobin drop between the drain group (1.1±0.6 g/dl) and the no-drain group (1.3±0.8 g/dl) (p=0.142). Both groups showed comparable preoperative hemoglobin levels and postoperative outcomes. Conclusions: Closed negative suction drainage does not significantly impact postoperative hemoglobin levels within the first 24 hours following total knee arthroplasty, suggesting that routine drain use may not be essential for blood conservation in this patient population.